Policy Uncertainty and Mergers and Acquisitions in China - kang, chenlei (2019)
This study examines the relationship between policy uncertainty and M&A. 5669 M&A deals over period 2000-2018 are used. The results show that there is no relationship between policy uncertainty and time to complete M&A deals. Acquirers are less likely to use stock only as payment method during policy uncertain period than other payment methods, at the same time, the acquirers are more likely to use cash only as payment method during policy uncertain period than other payment methods. In addition, making acquisition during policy uncertain period increase the shareholder’s wealth, and this effect is more pronounced for SOEs.